2010
DOI: 10.1080/10911351003751918
|View full text |Cite
|
Sign up to set email alerts
|

An Ecological Approach to Understanding Youth Violence: The Mediating Role of Substance Use

Abstract: The authors tested an ecological model that posits mediating variables (substance use and mental health) in the association between ecological factors (family closeness, school closeness, and peer closeness) and youth violence in a sample of 4,783 adolescents. Model including substance use present significantly less total effect between ecological factors and youth violence than do models without substance use. Additional probing of significant mediation effect using the Sobel test was performed and suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…Some studies reported that poor parent-children relationships and communications increased the probability of victimization by bullying (Bowers et al 1994; Moon et al 2010; Stevens et al 2002). Jaynes (2008) found that parental involvement was a predictor of being bullied by investigating the relationship between parental involvement and being bullied among 7th to 12th grade students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies reported that poor parent-children relationships and communications increased the probability of victimization by bullying (Bowers et al 1994; Moon et al 2010; Stevens et al 2002). Jaynes (2008) found that parental involvement was a predictor of being bullied by investigating the relationship between parental involvement and being bullied among 7th to 12th grade students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Moon, Patton and Rao (2011) noted that susceptibility to adversity is heightened during this period of accelerated maturation and social transition, in the human life cycle. Of several problem behaviors observed at this age, youth offending is becoming the most pressing issue throughout the world.…”
Section: Background Of the Researchmentioning
confidence: 99%
“…Important eco developmental predictors of substance use emerge from a number of social levels and systems. For example, processes occurring within the family, such as communication (Noyori-Corbett & Moon, 2010), support (Guerrero et al, 2010), and positive parental involvement (Moon, Patton, & Rao, 2010) are negatively predictive of adolescent substance use and violence. Moreover, a number of studies have indicated that provision of parental warmth and support is associated with less adolescent substance use (Cleveland, Feinberg, & Greenber, 2010).…”
Section: Eco Developmental Influences On Substance Usementioning
confidence: 99%
“…Furthermore, adolescents who had more time to spend with their parents had a tendency to show lower rates of alcohol and other substance use (Crawford & Novak, 2002;Hadley et al, 2016;Kuendig & Kuntsche, 2006). Similarly, processes occurring at school, such as school bonding and interest (Moon, Patton, & Rao, 2010), and processes occurring in the peer network, such as association with deviant or risk-taking peers (Casey & Beadnell, 2010), have been found to be strongly related to adolescent substance use. Processes that do not directly involve the adolescent are also predictive of adolescent substance use.…”
Section: Eco Developmental Influences On Substance Usementioning
confidence: 99%
See 1 more Smart Citation